Morphologic characterization of pulmonary nodules with ultrashort TE MRI at 3T - Wielpütz, Mark Oliver; Kauczor, Hans-Ulrich (American journal of roentgenology, 2018)
Objective: Ultrashort TE (UTE) MRI has been shown to deliver high-resolution images comparable to CT images. Here we evaluate the potential of UTE-MRI for precise lung nodule characterization. Subjects and methods: Fifty-one patients (mean [± SD] age, 68.7 ± 10.8 years) with 119 nodules or masses (mean size, 17.4 ± 16.3 mm; range, 4–88 mm) prospectively underwent CT (1-mm slice thickness) and UTE-MRI (TE, 192 μs; 1 mm3 resolution). Two radiologists assessed nodule dimensions and morphologic features (i.e., attenuation, margins, and internal lucencies), in consensus for CT and in a blinded fashion for UTE-MRI. Sensitivity, specificity, and kappa statistics were calculated in reference to CT. Results: Readers 1 and 2 underestimated the nodules' long axial diameter with UTEMRI by 1.2 ± 3.4 and 2.1 ± 4.2 mm, respectively (p < 0.001). The sensitivity and specificity of UTE-MRI for subsolid attenuation were 95.9% and 70.3%, respectively, for reader 1 and 97.1% and 71.4%, respectively, for reader 2 (κ = 0.71 and 0.68). With regard to margin characteristics, for lobulation, sensitivity was 70.6% and 54.9%, and specificity was 93.2% and 96.3% for readers 1 and 2, respectively; for spiculation, sensitivity was 61.5% and 48.0%, and specificity was 95.2% and 95.0%; and for pleural tags, sensitivity was 87.0% and 73.3%, and specificity was 93.8% and 95.0%. Finally, for internal lucencies, sensitivity was 72.7% and 61.3%, and specificity was 96.1% and 97.3% for readers 1 and 2, respectively (κ = 0.64–0.81 for reader 1 and 0.48–0.72 for reader 2). Interreader agreement for attenuation, margin characteristics, and lucencies was substantial to almost perfect with few exceptions (κ = 0.51–0.90). Conclusion: UTE-MRI systematically underestimated dimension measurements by approximately 1–2 mm but otherwise showed high diagnostic properties and interreader agreement, yet unprecedented by MRI, for nodule morphologic assessment.